The Effect Of Resistance Band Exercise On Leg Muscle Strength In Volleyball Of Muhammadiyah University Palopo Team - Ayyub Ayyub; Andi Heri Riswanto; Ahmad Ahmad; Rachmat Hidayat (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of resistance band training on leg muscle strength in volleyball athletes at the Muhammadiyah University of Palopo. The method used in this research is a one-group pre-test post-test design experiment with a quantitative approach from the results of a study that has been carried out on the effect of resistance band training on leg muscle strength in volleyball athletes at the Muhammadiyah University of Palopo. Moreover, the results of data processing with statistical analysis, the results of this study are sig values, namely 0.000 <0.05, which means that Ho is rejected. Thus, resistance band training significantly affects leg muscle strength in volleyball athletes at the Muhammadiyah University of Palopo.